Implementation of Transfers of Sale and Purchase Rights to Freehold Land and Registration - Anggri Rizky Pradhani (Sultan Agung Notary Law Review, 2020)
This study aims to: 1) To find out the procedures and procedures for the sale and purchase of freehold land and its registration at the Cirebon City Land Agency Office. 2) Obstacles that occur in the registration of the transfer of sale and purchase of property rights at the Cirebon City Land Agency Office. The approach method used in this research is the juridical empirical legal approach method. Research using the empirical juridical legal method is also called legal research regarding the enactment or implementation of normative legal provisions in action on any particular legal event that occurs in society. Based on the results of the data analysis, it is concluded that: 1. To make it easier to carry out legal actions of transferring property rights which are the objects of transfer to the right recipient, the transfer of rights must be carried out before the Land Deed Making Official who makes the deed and registered at the Land Office. In making a deed of sale and purchase of land rights, the seller, the buyer and witnesses must attend. Two pieces of land deeds issued by PPAT are made, all of which are original. One sheet is kept at the PPAT Office, the other sheet is submitted to the Head of the Land Office for registration purposes. The parties were only given a copy. 2. Obstacles originating from internal factors, causing the community to feel disappointed because the registration service for the transfer of land rights seems slow, While the obstacles originating from external factors, there are still many people who do not make the transfer of their land rights before the PPAT and at the same time do not register the transfer at the Land Office.